THE INFLUENCE OF PERSONAL COST, ORGANIZATIONAL COMMITMENT, ETHICAL SENSITIVITY, AND LOCUS OF CONTROL ON WHISTLEBLOWING INTENSITY IN THE GOVERNMENT OF NORTH SUMATRA PROVINCE - Mutia Widya Sari Dalimunthe; Eka Nurmala; Prawidya Hariani (Jurnal Ekonomi, 2023)
The aim of this study is to determined and analyzed whether the personal cost of research is to determine and analyzed whether the personal cost has influenced through the intencity Whistleblowing. To determined and analyzed whether the sensitivity has innfluenced through the intencity of whistleblowing. To determined anad analyzed whther locus of control has influency through Intencity of Whistleblowing. The research approach by using SmartPLS.3 software that was running by computer. The instrument of research was use questionnaire. The measuring scale in this research using the ordinale scale, Likert Scale. The sample of this reseacrh has 30 OPD in principal government of North Sumatera and the respodent of this research was 3 people each OPD and it has 90 people in accounting field, and the employee who working as the cheaf from accounting field. Based on this reseach personal cost, the organization commitments, the sensitivity ethic and locus of control has the influency through the Intensity of Whistleblowing to Principal Government of North Sumatera.